Dual-wavelength multifrequency photothermal wave imaging combined with optical coherence tomography for macrophage and lipid detection in atherosclerotic plaques using gold nanoparticles - Wang, Tianyi (Society of Photo-Optical Instrumentation Engineers, 2012)
The objective of this study was to assess the ability of combined photothermal wave (PTW) imaging and optical coherence tomography (OCT) to detect, and further characterize the distribution of macrophages (having taken up plasmonic gold nanorose as a contrast agent) and lipid deposits in atherosclerotic plaques. Aortas with atherosclerotic plaques were harvested from nine male New Zealand white rabbits divided into nanorose- and saline-injected groups and were imaged by dual-wavelength (800 and 1210 nm) multifrequency (0.1, 1 and 4 Hz) PTW imaging in combination with OCT. Amplitude PTW images suggest that lateral and depth distribution of nanorose-loaded macrophages (confirmed by two-photon luminescence microscopy and RAM-11 macrophage stain) and lipid deposits can be identified at selected modulation frequencies. Radiometric temperature increase and modulation amplitude of superficial nanoroses in response to 4 Hz laser irradiation (800 nm) were significantly higher than native plaque ([Formula: see text]). Amplitude PTW images (4 Hz) were merged into a coregistered OCT image, suggesting that superficial nanorose-loaded macrophages are distributed at shoulders on the upstream side of atherosclerotic plaques ([Formula: see text]) at edges of lipid deposits. Results suggest that combined PTW-OCT imaging can simultaneously reveal plaque structure and composition, permitting characterization of nanorose-loaded macrophages and lipid deposits in atherosclerotic plaques.